Clinical and Health Outcomes Initiative in Comparative Effectiveness for Bipolar Disorder (Bipolar CHOICE): A pragmatic trial of complex treatment for a complex disorder. (February 2014) - Nierenberg, Andrew A; Sylvia, Louisa G; Leon, Andrew C; Reilly-Harrington, Noreen A; Shesler, Leah W; McElroy, Susan L; Friedman, Edward S; Thase, Michael E; Shelton, Richard C; Bowden, Charles L; Tohen, Mauricio; Singh, Vivek; et al.
Background: Classic and second-generation antipsychotic mood stabilizers are recommended for treatment of bipolar disorder, yet there are no randomized comparative effectiveness studies that have examined the 'real-world' advantages and disadvantages of these medications. Purpose: We describe the strategic decisions in the design of the Clinical and Health Outcomes Initiative in Comparative Effectiveness for Bipolar Disorder (Bipolar CHOICE). This article outlines the key issues and solutions the investigators faced in designing a clinical trial that would maximize generalizability and inform real-world clinical treatment of bipolar disorder. Methods: Bipolar CHOICE was a 6-month, multi-site, prospective, randomized clinical trial of outpatients with bipolar disorder. This study compares the effectiveness of quetiapine versus lithium, each with adjunctive personalized treatments (APTs). The co-primary outcomes selected are the overall benefits and harms of the study medications (as measured by the Clinical Global Impression-Efficacy Index) and the Necessary Clinical Adjustments (a measure of the number of medication changes). Secondary outcomes are continuous measures of mood, the Framingham General Cardiovascular Risk Score, and the Longitudinal Interval Follow up Evaluation Range of Impaired Functioning Tool (LIFE-RIFT). Results: The final study design consisted of a single-blind, randomized comparative effectiveness trial of quetiapine versus lithium, plus APT, across 10 sites. Other important study considerations included limited exclusion criteria to maximize generalizability, flexible dosing of APT medications to mimic real-world treatment, and an intent-to-treat analysis plan. In all, 482 participants were randomized to the study, and 364 completed the study. Limitations: The potential limitations of the study include the heterogeneity of APT, selection of study medications, lack of a placebo-control group, and participants' ability to pay for study medications. Conclusion: We expect that this study will inform our understanding of the benefits and harms of lithium, a classic mood stabilizer, compared to quetiapine, a second-generation antipsychotic with broad-spectrum activity in bipolar disorder, and will provide an example of a well-designed and well-conducted randomized comparative effectiveness clinical trial.